Associação entre a força da preensão manual e depressão - Mignoni, Ismael (2022)
Previous studies demonstrate the association between Handgrip Strength (HGS) with the risk of developing depression. However, the previous meta-analyses on the topic took methodological decisions that may lead to biased estimates. The present study aimed to evaluate the association between HGS and the incidence of depression through a meta-analysis. Studies evaluating the association between HGS, assessed using a hand-held dynamometer, and incident depression in adults were eligible for the study. The study was registered in PROSPERO under the ID: CRD42022336752. The databases used to search for included studies were: Embase, Psycinfo, Web Of Science, Sportdiscus and Pubmed, until July 4, 2022. The search resulted in 1987 studies, of which eleven were included in the meta-analysis, accounting for 556,749 individuals, with an average age of 44.33 years old. Through a meta-analysis of random effects, it was identified that people with higher HGS are 29% less likely to develop incident depression when compared to those with lower HGS (OR = 0.702, CI = 0.670-0.736, P < 0.001). Both the Begg-Mazumdar Kendall test (Tau = -0.090, P = 0.697) and the Egger's test (Intercept = -0.073, P = 0.877) and the visual analysis of the funnel plot did not identify the presence of publication bias. According to the Failsafe N test, 331 studies with negative results are required to make the association not statistically significant. The present findings support the notion that higher HGS is prospectively associated with lower risk of incident depression.